A method for the chemical looping cycle decomposition of potassium fluosilicate for co-production of potassium fluoride and silicon dioxide
Patent Information
- Application Number
- CN202611185985.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-08-06
AI Technical Summary
[0005]本发明的目的在于:解决现有直接水解法存在的高温严重腐蚀问题,以及传统氨解法中生成的硅胶极难过滤的问题
[0015] 1. This invention improves the filtration throughput of silica compared to existing technologies and reduces washing water consumption by more than 85%; at the same time, it drastically reduces the main reaction temperature for releasing hydrogen fluoride from over 1000℃ to 450-550℃.
Smart Images

Figure CN122667602B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of inorganic fluorosilicone chemical technology, and more specifically to a method for the chemical chain cycle decomposition of potassium fluorosilicate to co-produce potassium fluoride and silicon dioxide. Background Technology
[0002] Potassium fluorosilicate is a major byproduct of wet-process phosphoric acid production and the fluoride salt industry, rich in fluorine, silicon, and potassium. Achieving its high-value decomposition is a key technological milestone in the fluorochemical industry.
[0003] For the decomposition of this substance, existing technologies mainly employ the following two routes, both of which suffer from serious process defects: First, the direct high-temperature hydrolysis method. Water vapor is directly introduced into the system. Due to the extremely high Si-F bond energy, the activation energy for bond breaking during hydrolysis is extremely high. Its drawback is that the reaction needs to be maintained at an extreme high temperature above 1000℃, resulting in enormous energy consumption. Furthermore, the water vapor and hydrogen fluoride mixture generated at this high temperature are highly corrosive, leading to severe intergranular corrosion and perforation in the alloy reaction equipment. Second, the ammonolysis and alkaline circulation method. The reaction is carried out in the liquid phase using ammonia water. Its drawback is that the SiO2 precipitated in the aqueous solution inevitably undergoes hydration, forming a three-dimensional network of silica gel containing a large number of silanol groups (-OH). This colloid has strong water-holding and thixotropic properties, instantly forming a dense, impermeable layer on industrial filter cloth, making filtration extremely difficult, and the washing water consumption is typically more than 20 times the product mass.
[0004] Therefore, it is necessary to propose a method for the chemical chain decomposition of potassium fluorosilicate to co-produce potassium fluoride and silicon dioxide to solve the above problems. Summary of the Invention
[0005] The purpose of this invention is to solve the problem of severe high-temperature corrosion in existing direct hydrolysis methods, and the problem of the extremely difficult filtration of silica gel generated in traditional ammonolysis methods.
[0006] To achieve the above objectives, the present invention specifically adopts the following technical solution: A method for the chemical chain-cycle decomposition of potassium fluorosilicate to co-produce potassium fluoride and silicon dioxide, using at least one selected from zirconium dioxide and titanium dioxide as a solid oxygen carrier, includes the following steps: (1) Displacement reaction: Potassium fluorosilicate is mixed with the solid oxygen carrier and calcined at a temperature of 450°C to 700°C to produce solid silica and potassium fluorometal complex containing the corresponding group IVB metal elements. (2) Separation: The reaction product obtained in step (1) is extracted with hot water, and the silica product and the hot filtrate rich in the potassium fluoride complex are obtained by solid-liquid separation; (3) Crystallization: The hot filtrate is cooled and crystallized to precipitate potassium fluoride complex crystals, and the potassium fluoride complex crystals are obtained by solid-liquid separation; (4) Hydrolysis and regeneration: The potassium fluoride complex crystals separated in step (3) are calcined and hydrolyzed by passing steam through them at a temperature of 400°C to 600°C, releasing hydrogen fluoride gas and generating solid potassium fluoride. At the same time, the potassium fluoride complex crystals are hydrolyzed and regenerated into the solid oxygen carrier. (5) Product collection and recycling: Collect the hydrogen fluoride gas; after washing and filtering the reaction product generated in step (4) to separate the potassium fluoride product, recycle the regenerated solid oxygen carrier back to step (1) for use.
[0007] This invention constructs a transition metal solid oxygen support chemical chain, breaking down the difficult-to-break Si-F bond into a two-step mild reaction. In step (1), in an anhydrous high-temperature solid-phase environment, oxygen atoms are directly provided to silicon by the support lattice. Due to the lack of free water, the coordination conditions for the formation of silica gel are completely destroyed, promoting the in-situ crystallization of SiO2. In step (4), the extremely low hydrolysis activation energy of the fluorine metal complex K2ZrF6 is utilized to achieve efficient fluorine release and support regeneration at low temperatures.
[0008] Further, the IVB group transition metal oxide mentioned in step (1) is zirconium dioxide or titanium dioxide; when the solid oxygen support is zirconium dioxide, the generated potassium fluoride complex is potassium fluorozirconate; when the solid oxygen support is titanium dioxide, the generated potassium fluoride complex is potassium fluorotitanate.
[0009] Furthermore, in the mixing and calcination in step (1), anhydrous potassium fluoride is added as a flux at a rate of 5% to 15% of the total mass of the mixture.
[0010] Furthermore, the roasting temperature in step (1) is 550°C to 650°C.
[0011] Furthermore, the temperature of the hot water immersion in step (2) is 85°C to 100°C.
[0012] Furthermore, the cooling crystallization temperature in step (3) is from 0°C to 25°C.
[0013] Furthermore, the temperature of the roasting and hydrolysis in step (4) is 450°C to 550°C.
[0014] Beneficial effects:
[0015] 1. This invention improves the filtration throughput of silica compared to existing technologies and reduces washing water consumption by more than 85%; at the same time, it drastically reduces the main reaction temperature for releasing hydrogen fluoride from over 1000℃ to 450-550℃.
[0016] 2. This invention alters the thermodynamic pathway of the reaction by introducing ZrO2 and other materials as a support. Practical results show that this method not only successfully removes fluoride, but also, due to the reaction occurring in a high-temperature solid-phase microenvironment, the generated silica spontaneously forms dense crystals, defying the expectation that conventional wet processes inevitably produce gels.
[0017] 3. When the substitution calcination temperature is below 450℃, oxygen-fluorine lattice exchange is difficult to occur, and the conversion rate is less than 15%. However, when the temperature is close to 450-550℃, due to the synergistic diffusion effect of flux KF, the reaction rate of the system changes abruptly, and the conversion rate rapidly increases to over 98%, achieving efficient separation at medium and low temperatures. Attached Figure Description
[0018] Figure 1 This is a flowchart of the method of the present invention. Detailed Implementation
[0019] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0020] To facilitate accurate understanding and reproduction of the test data of this invention by those skilled in the art, the calculation principles and formulas of the core evaluation indicators involved in the embodiments and comparative examples are as follows: K2SiF6 conversion rate ( Based on the material balance of silicon, the calculation formula is: ; In the formula: The conversion rate of potassium fluorosilicate is expressed as a percentage (%). or : This indicates the actual mass of dried silica obtained after hot water leaching, solid-liquid separation, and drying following the reaction, expressed in grams (g). : This indicates the mass of silicon dioxide that can be produced by the initial input of potassium fluorosilicate in a theoretically complete reaction according to stoichiometry, expressed in grams (g). : This indicates the molar mass of silicon dioxide (SiO2), with a value of 60.08 g / mol; : indicates the initial mass of dry potassium fluorosilicate added in reaction step (1), in grams (g); : This indicates the molar mass of potassium fluorosilicate (K2SiF6), with a value of 220.27 g / mol.
[0021] Same pressure difference filtration flux ( ): The fixed vacuum filtration pressure difference is -0.08MPa, and the pore size is... The effective filtration area A = 0.00785m² 2 The standard filter paper, the formula is: ; In the formula : Indicates the solid-liquid separation filtration flux under the same negative pressure difference, in liters per square meter per hour (L / m²) 2 .h); : Indicates the volume of clarified filtrate collected during the filtration process, in liters (L). A: Indicates the effective filtration area of the filtration equipment, which is fixed at 0.00785m² in this test. 2 ; t: represents the volume collected at a differential pressure of -0.08 MPa. The time taken for the filtrate to be processed, expressed in hours (h). Unit SiO2 washing water consumption ( ): The filter cake was washed until the effluent could not be detected by electrodes. - (≤1ppm), the formula is: ; In the formula : This indicates the amount of deionized water consumed in the production of one unit mass of silica product, expressed in liters per kilogram (L / kg). : indicates that the filter cake is rinsed into the washing effluent. - The total volume of deionized water consumed when the concentration is less than or equal to the specified concentration, expressed in liters (L). : Indicates the final mass of dry silica product obtained after washing and drying, in kilograms (kg).
[0022] Recovery rate of potassium fluoride metal complex crystals (K2ZrF6 / K2TiF6) ), Principle: The ratio of the actual mass of the complex crystals obtained after cooling crystallization and drying to the theoretical mass of the reaction product in step (1) is determined. Calculation formula: ; In the formula : Indicates the crystallization recovery rate of potassium fluoride metal complex crystals obtained by cooling crystallization separation, expressed as a percentage (%). : This indicates the actual mass of potassium fluoride metal complex crystals (K2ZrF6 or K2TiF6) obtained after cooling crystallization, centrifugation dehydration and drying, in grams (g). : indicates the mass of potassium fluorine metal complex to be generated based on the theoretical calculation of the amount of reactant K2SiF6 and the conversion rate in step (1), in grams (g).
[0023] Example 1: ZrO2 was used, with displacement at 600℃ and hydrolysis at 500℃.
[0024] (1) Displacement reaction: 220.3 g (1 mol) of dry K2SiF6 powder, 123.2 g (1 mol) of ZrO2 powder and 38.2 g of anhydrous KF (accounting for about 10% of the total mass of the mixture) were mixed evenly. The mixture was placed in a muffle furnace and calcined at 600 °C for 2.0 hours to produce solid silica and potassium fluorozirconate (K2ZrF6).
[0025] (2) Separation: The clinker was discharged into a reactor lined with Teflon, deionized water was added, and the mixture was heated to 95°C and stirred for 30 minutes. Filtering was performed under a pressure difference of -0.08 MPa to complete solid-liquid separation. After washing and drying the filter cake, 59.5 g of dense crystalline SiO2 was obtained, and the K2SiF6 conversion rate was calculated to be 99.1%. The filtration flux under the same pressure difference was measured to be 820 L / (m²). 2 The unit SiO2 washing water consumption is 1.6 L / kg (·h).
[0026] (3) Crystallization: The hot filtrate rich in K2ZrF6 was cooled to 15℃ at a rate of 2℃ / min to precipitate white crystals. After centrifugation and dehydration, 275.0g of K2ZrF6 crystals were obtained. The crystallization recovery rate was 97.0% and the purity was 99.4%.
[0027] (4) Hydrolysis and regeneration: The separated K2ZrF6 crystals are placed in a tube furnace and calcined and hydrolyzed at 500°C with superheated steam for 2 hours to generate solid KF. The complex is then hydrolyzed and regenerated into solid ZrO2 oxygen carrier.
[0028] (5) Product collection and recycling: The hydrogen fluoride gas released by hydrolysis is collected by condensation to obtain 78.5g of anhydrous HF. The bottom material is washed with water to extract KF product; the ZrO2 powder regenerated after washing and drying is directly recycled back to step (1) for the next batch.
[0029] Example 2: TiO2 was used, with replacement at 450℃ and hydrolysis at 400℃.
[0030] (1) Displacement reaction: 1 mol K2SiF6 was mixed with 1 mol TiO2 (79.9 g), and 5% anhydrous KF was added to the mixture. The mixture was calcined at 450 °C for 4.5 hours to produce solid silica and potassium fluorotitanate (K2TiF6).
[0031] (2) Separation: Deionized water was added, and hot water extraction was performed at 85℃. Vacuum filtration was conducted under a pressure difference of -0.08 MPa to obtain 57.1 g of dense crystalline SiO2, with a conversion rate of 95.2%. The filtration flux under the same pressure difference was measured to be 650 L / (m²). 2 The unit SiO2 washing water consumption is 2.1 L / kg (·h).
[0032] (3) Crystallization: The hot filtrate was cooled to 0°C using an ice-water bath to crystallize potassium fluorotitanate (K2TiF6) crystals. 228.1g of K2TiF6 crystals were obtained by filtration. The crystallization recovery rate was 95.0% and the purity was 99.0%.
[0033] (4) Hydrolysis and regeneration: K2TiF6 crystals are hydrolyzed by passing water vapor through them at 400℃ for 4 hours, releasing HF gas and generating solid KF, which is then hydrolyzed and regenerated into TiO2.
[0034] (5) Product collection and recycling: Collect HF gas; after washing the hydrolysis product with water to separate KF, recycle the regenerated TiO2 oxygen carrier back to step (1) for use.
[0035] Example 3: ZrO2 was used, with displacement at 700℃ and hydrolysis at 600℃.
[0036] (1) Displacement reaction: 1 mol K2SiF6 and 1 mol ZrO2 were mixed, and KF flux accounting for 15% of the total mass of the mixture was added. The mixture was calcined at 700℃ for 0.8 hours to fully react and generate SiO2 and K2ZrF6.
[0037] (2) Separation: Hot water extraction was performed at 100℃ under slight boiling conditions, followed by filtration to obtain 59.8 g of coarse crystalline SiO2, with a conversion rate of 99.5%. The filtration flux under the same pressure difference was measured to be 880 L / (m²). 2 The unit SiO2 washing water consumption is 1.4 L / kg (·h).
[0038] (3) Crystallization: The hot filtrate was naturally cooled to room temperature of 25°C and crystallized, 278.1g of K2ZrF6 crystals were precipitated, the crystallization recovery rate was 98.1%, and the purity was 99.6%.
[0039] (4) Hydrolysis regeneration: The crystals are hydrolyzed by passing steam through water at 600°C for 1 hour to rapidly hydrolyze and regenerate ZrO2 and release HF.
[0040] (5) Product collection and recycling: Collect HF gas; separate KF products by water washing; and recycle the regenerated ZrO2 solid oxygen carrier.
[0041] Example 4: ZrO2 was used, with displacement at 550℃ and hydrolysis at 450℃.
[0042] (1) Displacement reaction: 1 mol K2SiF6 and 1 mol ZrO2 are mixed, 8% KF flux is added, and the mixture is calcined at 550℃ for 2.5 hours to generate SiO2 and K2ZrF6.
[0043] (2) Separation: Deionized water was added, and the mixture was extracted by hot water leaching at 90℃ and then filtered to obtain 59.1 g of crystalline SiO2, with a conversion rate of 98.4%. The filtration flux under the same pressure difference was measured to be 750 L / (m²). 2 The unit SiO2 washing water consumption is 1.8 L / kg (·h).
[0044] (3) Crystallization: The filtrate was cooled to 5°C to crystallize, and 273.6g of K2ZrF6 crystals were obtained. The crystallization recovery rate was 96.5% and the purity was 99.3%.
[0045] (4) Hydrolysis and regeneration: K2ZrF6 crystals are calcined and hydrolyzed by passing steam through them at 450°C for 3 hours to generate KF and regenerate ZrO2.
[0046] (5) Product collection and recycling: Collect HF gas; wash and filter the hydrolysis products to separate KF products, and regenerate ZrO2 and recycle it back to step (1).
[0047] Example 5: TiO2 was used, with displacement at 650℃ and hydrolysis at 550℃.
[0048] (1) Displacement reaction: 1 mol K2SiF6 and 1 mol TiO2 were mixed, 12% KF was added, and the mixture was calcined at 650℃ for 1.2 hours to generate SiO2 and K2TiF6.
[0049] (2) Separation: Hot water extraction at 98℃ and filtration yielded 59.3 g of crystalline SiO2, with a conversion rate of 98.8%. The filtration flux under the same pressure difference was measured to be 800 L / (m²). 2 The unit SiO2 washing water consumption is 1.5 L / kg (·h).
[0050] (3) Crystallization: The filtrate was cooled to 20℃ to crystallize, and 232.4g of K2TiF6 crystals were obtained. The crystallization recovery rate was 96.8% and the purity was 99.2%.
[0051] (4) Hydrolysis and regeneration: K2TiF6 crystals are hydrolyzed by passing steam through them at 550°C for 1.5 hours to generate KF and regenerated TiO2.
[0052] (5) Product collection and recycling: HF gas is collected, KF product is obtained by water washing and separation, and the regenerated TiO2 oxygen carrier is recycled.
[0053] Comparative Example 1: Traditional ammonolysis method.
[0054] (1) Ammonolysis reaction: 10% excess concentrated ammonia was slowly added to 1 mol (220.3 g) of K2SiF6, and the mixture was stirred at 60 °C for 2 hours. The system rapidly formed a viscous, transparent hydrated silica gel. The conversion rate of K2SiF6 was measured to be 98.0%.
[0055] (2) Separation test: Solid-liquid separation was performed using the same -0.08MPa differential pressure filtration equipment as in Example 1. The filter cloth was completely clogged by silica gel within tens of seconds, making filtration impossible. The measured filtration flux under the same differential pressure was <25L / (m²). 2 ·h), the unit SiO2 washing water consumption is >25.0 L / kg.
[0056] (3) Explanation of the interruption of subsequent steps: Due to the strong water retention of silica gel and the inability to achieve efficient solid-liquid separation, a clear filtrate could not be obtained, which made it impossible to carry out the subsequent cooling crystallization, complex separation and hydrolysis cycle steps. The washing water consumption required to remove residual fluoride salts in the colloid was as high as 15.0L (i.e. 25.0L / kg SiO2), which is more than 10 times that of Example 1.
[0057] Comparative Example 2: Direct high-temperature hydrolysis method.
[0058] (1) Direct hydrolysis attempt: 1 mol of K2SiF6 was placed in a high-temperature alloy reactor and superheated steam was directly introduced. The reaction was carried out at 500℃ for 2 hours, and no HF gas was detected to escape.
[0059] (2) Forced heating test: After the temperature was forcibly raised to 1100℃, the Si-F bond broke and fluorine was released. However, the highly corrosive mixed gas rapidly eroded the reactor, and the inner wall suffered intergranular corrosion and perforation damage with a depth of 0.5mm. The equipment was destroyed and scrapped, and the experiment was forced to stop.
[0060] (3) Explanation of interruption of subsequent steps: Due to the lack of solid oxygen carrier to construct chemical chain, no fluorine metal complex intermediate was generated, the reactor was damaged, and the cooling crystallization and closed-loop circulation steps could not be carried out.
[0061] Summary table of core data test results for both the example and comparative examples: To visually demonstrate the support effect of each parameter endpoint of this invention and its essential differences from existing technologies, the core data of each experimental group are summarized as follows: Oxygen carrier / flux ratio <![CDATA[ZrO2 / 10%]]> <![CDATA[TiO2 / 5%]]> <![CDATA[ZrO2 / 15%]]> <![CDATA[ZrO2 / 8%]]> <![CDATA[TiO2 / 12%]]> none none Displacement / Leaching Temperature 600℃ / 95℃ 450℃ / 85℃ 700℃ / 100℃ 550℃ / 90℃ 650℃ / 98℃ 60℃ not applicable Crystallization / hydrolysis temperature 15℃ / 500℃ 0℃ / 400℃ 25℃ / 600℃ 5℃ / 450℃ 20℃ / 550℃ not applicable not applicable <![CDATA[Conversion Rate of K2SiF6 (%)]]> 99.1 95.2 99.5 98.4 98.8 98.0 Corrosion interruption <![CDATA[Morphology of SiO₂ product]]> dense crystals dense crystals coarse crystals dense crystals dense crystals Viscous hydrated silicone vaporization or gelation <![CDATA[Filter flux at the same pressure difference (L / (m 2 ·h))]]> 820 650 880 750 800 <25 not applicable <![CDATA[Water consumption per unit SiO₂ for water washing (L / kg)]]> 1.6 2.1 1.4 1.8 1.5 >25.0 not applicable Recovery rate of complex crystals (%) 97.0 95.0 98.1 96.5 96.8 not applicable not applicable Purity of the complex crystal (%) 99.4 99.0 99.6 99.3 99.2 not applicable not applicable Reactor corrosion evaluation Extremely small Non-corrosive slight Extremely small Extremely small Mild Destructive intercrystalline perforation In summary, the present invention, through the detailed chemical chain cycle parameter ranges in the specification, can effectively achieve the intended technical effects, demonstrating outstanding and undeniable progress.
[0062] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. The scope of patent protection of the present invention shall be determined by the claims. Similarly, any equivalent structural changes made based on the content of the present invention's specification shall also be included within the scope of protection of the present invention.
Claims
1. A method for the chemical chain-recycling decomposition of potassium fluorosilicate to co-produce potassium fluoride and silicon dioxide, characterized in that, Using at least one selected from zirconium dioxide and titanium dioxide as a solid oxygen carrier, the method includes the following steps: (1) Displacement reaction: Potassium fluorosilicate is mixed and calcined with the solid oxygen carrier at a temperature of 450°C to 700°C. Anhydrous potassium fluoride of 5% to 15% of the total mass of the mixture is added as a flux during the mixed calcination to produce solid silica and potassium fluorometallic complex containing the corresponding group IVB metal elements. (2) Separation: The reaction product obtained in step (1) is extracted with hot water, and the silica product and the hot filtrate rich in the potassium fluoride complex are obtained by solid-liquid separation; (3) Crystallization: The hot filtrate is cooled and crystallized to precipitate potassium fluoride complex crystals, and the potassium fluoride complex crystals are obtained by solid-liquid separation; (4) Hydrolysis and regeneration: The potassium fluoride complex crystals separated in step (3) are roasted and hydrolyzed by passing steam through them at a temperature of 400°C to 600°C. The roasting and hydrolysis temperature is 450°C to 550°C. Hydrogen fluoride gas is released and solid potassium fluoride is generated. At the same time, the potassium fluoride complex crystals are hydrolyzed and regenerated into the solid oxygen carrier. (5) Product collection and recycling: Collect the hydrogen fluoride gas; after washing and filtering the reaction product generated in step (4) to separate the potassium fluoride product, recycle the regenerated solid oxygen carrier back to step (1) for use.
2. The method for chemically cycling decomposition of potassium fluorosilicate to co-produce potassium fluoride and silicon dioxide according to claim 1, characterized in that, In step (1), when the solid oxygen support is zirconium dioxide, the generated potassium fluorometallic acid complex is potassium fluorozirconate; when the solid oxygen support is titanium dioxide, the generated potassium fluorometallic acid complex is potassium fluorotitanate.
3. The method for chemically cycling decomposition of potassium fluorosilicate to co-produce potassium fluoride and silicon dioxide according to claim 1, characterized in that, The roasting temperature in step (1) is 550°C to 650°C.
4. The method for chemically cycling decomposition of potassium fluorosilicate to co-produce potassium fluoride and silicon dioxide according to claim 1, characterized in that, The temperature of the hot water immersion in step (2) is 85°C to 100°C.
5. The method for chemically cycling decomposition of potassium fluorosilicate to co-produce potassium fluoride and silicon dioxide according to claim 1, characterized in that, The cooling crystallization temperature in step (3) is from 0°C to 25°C.
Citation Information
Patent Citations
Method for preparing high-purity potassium fluoride and co-producing white carbon black by adopting potassium fluosilicate
CN103112873A
Method for preparing potassium fluoride by utilizing potassium fluosilicate
CN103121699A